Association between time of delivery and composite adverse outcomes in pregnancies complicated by hypertensive disorders. (3rd July 2021) - Wagner, Stephen M.; Chen, Han-Yang; Gupta, Megha; Bicocca, Matthew J.; Mendez-Figueroa, Hector; Chauhan, Suneet P.
ABSTRACT: Introduction: A potential manner to lower the morbidity with the hypertensive disoreders of pregancy is to explore the time of day of delivery. Objective: To compare composite neonatal adverse outcomes among term women with hypertensive disorders. Methods: This population-based cohort study used the U.S. vital statistics dataset from 2013 to 2017. Time of delivery was categorized into three shifts. The primary outcome was composite neonatal adverse outcome.. Results: Compared to neonates delivered at the first shift, the risk of composite neonatal adverse outcome was higher at the third shift (aRR = 1.19, 95% CI = 1.13–1.25). Conclusion: the risk of composite neonatal adverse outcome is higher if the delivery occurs at the third (23:00–7:00) shift.